Assessment of a commercial gas hydrate inhibitor using the 3-in-1 technique (2018)
The ability of the novel 3-in-1 reactor to assess a commercial hydrate inhibitor was evaluated. Methane hydrates were formed using a mass fraction of 0.1 % of an unknown commercial inhibitor at constant pressure and different driving forces. Phase equilibria, kinetics, and morphology of the methane hydrates in the inhibited system were studied. The technique provided reproducible data on these three different aspects. The technique allowed to identify that the unknown inhibitor behaves as a kinetic hydrate inhibitor (KHI) for subcoolings more than 3.0 K. The uncertainty of the hydrate film growth rate for a specific subcooling varies. In addition, it was possible to confirm inhibitor A1 as a KHI since the value of T_HLV = 280.3 K ¿ 0.03 K is within the 95 % of prediction interval of the equilibrium temperature for the uninhibited system at the experimental pressure. Also, the experimental set up enabled morphological studies of the inhibited system which suggested that dendrites are less densely packed as subcooling decreases. Furthermore, one feature throughout the experiments could be noticed corresponding to the decrease in initial growth points and methane guest bubbles from cycle to cycle. Besides, the coverage time of hydrate on the surface of the droplet increases each reformation as a result of fewer initial growth points. Based on the above, the 3-in-1 technique was found to provide quick and reproducible information on the inhibition performance and could be used for further inhibition studies on gas hydrates